Application Of Biodiesel Fuel For Assessing Roadworthiness: A Study Focused On Hong Kong - Maolin, Yang; Nizamuddin Inamdar, Mohammad; Rashdi, Nur Syaza Binti (Cuestiones de Fisioterapia, 2023)
Placing A Specific Emphasis On The Function Of Refuelling Infrastructure, This Study Investigated The Application Of Biodiesel As A Fuel For Determining The Roadworthiness Of Hong Kong. The Research Was Motivated By The Growing Worries Regarding The Deterioration Of The Ecosystem, Outputs Of Greenhouse Gases, And Dependency On Fossil Fuels, All Of Which Created Hurdles To The Implementation Of Environmentally Friendly Urban Transit. The Use Of Biodiesel, Which Is Derived From Natural Resources Like Vegetative Oils, Leftover Cooking Fuels, And Animal-Derived Fats, Was Investigated As A More Environmentally Friendly Substitute That Has The Potential Of Contributing To The Reduction Of Polluting Emissions While Retaining The Functionality Of Vehicles. A Method Of Quantitative Analysis Was Used, And Standardised Questionnaires Were Used To Gather Data From A Representative Group Of Participants In Hong Kong. The Collection Of Data Was Carried Out Utilising The Questionnaires. The Questionnaire Gathered Responses From Individuals Addressing Their Views Of The Availability, Price, Dependability, And Effect That Biodiesel Has On Roadworthiness. The Association Among Refuelling Infrastructure And Automobile Security, Effectiveness And Adherence To Governmental Criteria Was Evaluated Using Both Descriptive Techniques. According To The Results, The Accessibility And Standard Of Refuelling Infrastructure Had A Beneficial Impact On The Widespread Use Of Biodiesel. In Addition To Ensuring Accordance With Strict Examination Criteria, Properly Maintained And Easily Available Infrastructure Improved The Efficiency Of Vehicles, Decreased Production Hazards, And Improved Productivity. In Addition, The Research Revealed That Biodiesel Might Be In Line With Hong Kong's More Expansive Ecological Strategies Thanks To Its Ability To Reduce Emissions And Encourage The Utilisation Of Alternative Sources Of Energy.